An explorative cross-sectional study examining self-reported health and nutritional status of disadvantaged people using food banks in Germany. Issue 1 (December 2015) - Depa, Julia; Hilzendegen, Carolin; Tinnemann, Peter; Stroebele-Benschop, Nanette
Abstract Background Even in high-income countries some population groups depend on food banks to support their food intake. We aimed to explore and compare health and nutritional status of food bank clients (Tafel e.V.) in different cities in Germany. Methods In a cross-sectional study, self-reported health and nutritional status of food bank clients living in three cities (Berlin - capital, Ludwigsburg- affluent city, Fulda - small town) which differ in size, available income and poverty rate, were assessed and compared to survey variables of the low socioeconomic status population of national surveys (DEGS and GEDA). Results Across cities, food bank clients (N = 276, response rate of 21.5 %) did not differ in main socio-demographic characteristics (age, nationality, education, professional qualification, household income). Smoking, having at least one chronic illness, estimating their own health status as moderate to poor and low consumption of fruits and vegetables were common characteristics. Comparing selected variables with the low socioeconomic status population of DEGS and GEDA, differences were found for a higher prevalence of diabetes among food bank clients and a worse self-reported health status. Considerably lower fruit consumption and lower hypertension prevalence among female and lower overweight rates among male food bank clients were found. Conclusions Although people using food banks vary in socio-demographic background, no differences for main demographics across the cities were found. In addition, the study suggests that for some health- and nutrition-related variables, national surveys in Germany might underestimate socioeconomic differences.